Aspect of Art And Meaning of Staging The Traditional Dolanan Game In Sanggar Kebo Iwa Badung - I nyoman Subagia (Mudra Jurnal Seni Budaya, 2017)
This article is a summary of the results of research to review aspects of the art, the meaning of staging traditional games studio Kebo Iwa dolanan in Badung. To reveal deeply these aspects, used a qualitative approach with the active participation of observation techniques, in-depth interviews and document study. Based on the methodology, the research explained that the first philosophical meaning, both philosophical meaning, the religious meaning of the third, the fourth meaning of aesthetics, the fifth meaning of education, sixth and seventh pelestraian meaning of togetherness. Dolanan performed by a group of children, where there is a beauty in conveying messages of religious teachings to the public through the medium of art. Because art as a symbol of truth (satyam), chastity (sivam) and beauty (sundaram).Artikel ini adalah ringkasan hasil penelitian yang mengulas aspek seni, makna pementasan permainan tradisional dolanan di Sanggar Kebo Iwa Badung. Untuk mengungkap secara mendalam aspek-aspek tersebut, digunakan pendekatan kualitatif dengan teknik observasi partisipasi aktif,wawancara mendalam dan studi dokumen. Berdasarkan metodelogi, hasil penelitian menjelaskan bahwa pertama makna filosofis, kedua makna religius, ketiga makna estetika, keempat makna pelestarian, kelima makna pendidikan, dan keenam kebersamaan. Dolanan yang dibawakan oleh sekelompok anak-anak, di mana terdapat suatu keindahan di dalam penyampaian pesan-pesan ajaran agama kepada masyarakat melalui media seni. Karena seni sebagai simbol kebenaran (satyam), kesucian (sivam) dan keindahan (sundaram).